Comparison of three different self-expanding metal stents using rabbit models for the treatment of tracheal collapse - Kim,Ji-Hyun (2022)
ABSTRACT Purpose: To identify an optimal self-expandable metallic stent (SEMS) and verify whether a mechanically superior SEMS would result in better clinical outcomes in the treatment of tracheal collapse. Methods: We selected three SEMS (n = 8 each), including an S-type stent with a wire diameter of 0.006 inches (S6) and two D-type stents with wire diameters of 0.006 (D6) and 0.007 inches (D7). Twenty-four New Zealand White rabbits were divided into three equal groups. After the stents were deployed, the clinical signs were recorded daily, and radiographic examinations were performed monthly. All rabbits were euthanized after three months. Results: Two rabbits with S6 stents and one rabbit with a D7 stent died within three months because of stent migration or pneumonia. All rabbits with D6 stents survived for three months. On histological examination, the D6 group had the lowest inflammation score. Conclusions: Both clinically and histopathologically, the results with D-type stents with a wire diameter of 0.006 inches were superior to those of the other groups (p = 0.001). The use of an optimal intraluminal stent may improve the long-term clinical outcomes in the treatment of tracheal collapse in dogs.